Double-Vitrectomy for Optic Disc Pit Maculopathy - Francesco Pichi; Mariachiara Morara; Chiara Veronese; Andrea Lembo; Lucia Vitale; Antonio P. Ciardella; Paolo Nucci (Case Reports in Ophthalmology, 2012)
Background: The origin of the fluid and precise pathophysiology of optic pit maculopathy remain unclear. It has been suggested that submacular fluid originates either from vitreous or cerebrospinal fluid. We report a case of optic pit maculopathy which was unsuccessfully treated with vitrectomy and internal limiting membrane (ILM) peeling, and subsequently resolved with revision of vitrectomy and gas tamponade. Methods: We report a case of optic disc pit maculopathy, well documented by spectral- domain optical coherence tomography, before and after pars plana vitrectomy with ILM peeling, and its revision with gas tamponade. Results: After ILM peeling, there was no improvement either in visual acuity or in the tomographic aspect of the retina. A revision of the surgery was then needed and gas tamponade was performed, which resulted in a complete resolution of the optic pit maculopathy. Conclusion: The absence of improvement after ILM peeling during the first surgical procedure, accompanied by resolution of the clinical picture with gas tamponade during the second surgical procedure, sustained the hypothesis of a subarachnoidal origin of the fluid.